Analisa Perencanaan Kolom Bulat Beton pada Proyek Vihara Prasadha Jinadhammo Medan - Yuono, Hafiiz Putra (Portal: Jurnal Teknik Sipil, 2025)
Abstract — The column, which is a very important part of the structural system, functions as the main element that transfers the entire load of the building to the foundation. Columns serve as the primary structural members that carry the building’s self-weight, live loads, as well as wind and earthquake loads. The column design is carried out based on SNI 2847:2019, and the structural analysis is performed using the SAP2000 application, allowing the results to be examined and understood before proceeding to the next stage of construction. The analysis results show a column reinforcement design of 36D25 with a reinforcement area (As) of 17,678.58 mm², spiral tie area (Ds) of 340 mm², load factor (Pu) of 14,551 kNm, and nominal compressive strength (Pn) of 46,074 kg. The comparison between Pu and Pn indicates that the column’s capacity meets the required standards, thus the design is declared safe.